A Rare Case of Cardiac Metastatic Uterine Intravenous Leiomyomatosis - Wu, Xun; Li, Feng; Iroegbu, Chukwuemeka Daniel; Fan, Chengming; Song, GuoBao (Frontiers in Cardiovascular Medicine, 2022)
Intravenous leiomyomatosis (IVL) is a distinct uterine leiomyoma, even rare when combined with intracardiac invasion. Although leiomyomas are histologically benign, intracardiac metastasis may cause circulatory failure and death. Herein, we report a 55-year-old woman with a tricuspid chordae mass on echocardiography. Subsequently, gynecological ultrasonography revealed that the patient had masses in the ovaries, internal iliac vein, and inferior vena cava. The patient successfully underwent resection of the tricuspid chordae tendinea mass and implantation of the tricuspid annuloplasty ring. The patient underwent inferior vena cava, common iliac vein, hysterectomy, and bilateral adnexectomy after 4 months. To our knowledge, the present study is the first reported case with such a rare combination.